2004
DOI: 10.1111/j.1479-8077.2004.00057.x
|View full text |Cite
|
Sign up to set email alerts
|

Leflunomide in the treatment of rheumatoid arthritis and other autoimmune disorders

Abstract: Leflunomide (Arava) is an isoxazole derivative approved by the US Food and Drug Administration (FDA) for the treatment of rheumatoid arthritis (RA). Its mechanism of action is based on the inhibition of dihydroorotate dehydrogenase, an enzyme that controls the pathway for denovo synthesis of uridine ribose monophosphate (rUMP) in activated T-cells. Leflunomide is structurally unrelated to other known immunomodulatory drugs in clinical use. Data have demonstrated benefit in control of clinical symptoms and qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Chikura et al found that 75% of the reviewed cases had received steroids, 31% had received antimicrobial treatment, and 22% were treated with both steroids and antibiotics [12]. The elimination of leflunomide may be accelerated by cholestyramine, and this is a very promising treatment option [2,12,13]. Wong et al reported a case of successful treatment with cholestyramine in monotherapy administered orally in a dose of 8 g three times daily [14], but further convincing data on the efficacy of this drug in the treatment of leflunomide-induced lung injury are required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chikura et al found that 75% of the reviewed cases had received steroids, 31% had received antimicrobial treatment, and 22% were treated with both steroids and antibiotics [12]. The elimination of leflunomide may be accelerated by cholestyramine, and this is a very promising treatment option [2,12,13]. Wong et al reported a case of successful treatment with cholestyramine in monotherapy administered orally in a dose of 8 g three times daily [14], but further convincing data on the efficacy of this drug in the treatment of leflunomide-induced lung injury are required.…”
Section: Discussionmentioning
confidence: 99%
“…Leflunomide, a DMARD introduced more than a decade ago, was reported to alleviate RA symptoms and retard radiological progression of the disease [2]. However, adverse-event moni-toring revealed an increased risk of interstitial lung disease in predisposed individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Concurrent NSAID use may exacerbate this phenomenon. 18 Frequent blood pressure monitoring is often advised. Other adverse effects of leflunomide include nausea, diarrhoea and rash.…”
Section: Leflunomidementioning
confidence: 99%
“…It has a half life of around 15 days. 18 Elimination is via the gastrointestinal tract and kidneys. Teriflunomide goes through extensive enterohepatic recircula tion.…”
Section: Leflunomidementioning
confidence: 99%